An online counseling intervention for Nigerian undergraduates with academic burnout - Eseadi, Chiedu (Universitas Negeri Padang, 2022)
A growing problem among university students is academic burnout, and it has become more prevalent in recent years. With the increasing demand for school mental health services, online counseling interventions are gradually being regarded as a reasonable way to provide assistance to students with regard to burnout reduction. It was the researcher's aim to find out whether an online counseling intervention would be able to reduce academic burnout in a Nigerian undergraduate sample. A total of 80 Nigerian undergraduates were participants of this study. In this study, the participants were randomly assigned to the intervention group (n=40) and to the control group (n=40) by using a simple randomization procedure. For the collection of data, the Oldenburg Burnout Inventory for Students and the Students School Burnout Inventory were utilised. The researcher applied repeated measures ANOVA to examine within and between groups' mean differences, reported η² to establish treatment effect size, and conducted posthoc analyses where mean differences existed using Holm's approach. The results of the study demonstrate that the online counseling intervention for academic burnout was effective in reducing the level of academic burnout among Nigerian undergraduates.As online counseling can help students reduce academic burnout, this finding opens the door to reach a larger number of burned-out students, such as those who live off-campus or are afraid of social stigma when seeking mental health care. This intervention has the potential to significantly improve student mental health related to burnout in other higher education settings like polytechnics. It is recommended that students should be encouraged to receive psychological supports and care from the university's counseling centre, not just during crises, but as a regular process of mental health support.